2012
DOI: 10.1099/jmm.0.032946-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholangitis with septic shock caused by Raoultella planticola

Abstract: Raoultella planticola (formerly Klebsiella planticola) is a Gram-negative bacterium that has been rarely reported in association with human infection. Here we describe a case of cholangitis complicated with septic shock caused by R. planticola in an immunocompromised patient with advanced cancer who underwent endoscopic retrograde cholangiopancreatography to extract common bile duct stones. The infection was cleared by piperacillin-tazobactam treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 11 publications
2
36
0
1
Order By: Relevance
“…Similarities of our case to the six summarized by Yokota et al (2012) and the additional four reported by other authors (Castanheira et al, 2009;Kim et al, 2012;Teo et al, 2012) include an association with invasive procedures or trauma (8/11, ERCP in two), an intraabdominal focus (4/11, cholangitis/ cholecystitis in three) and malignancy (3/11). Of the ten previously reported cases of infection due to R. planticola, five involved a monobacterial bacteraemia (Castanheira et al, 2009;Freney et al, 1986;Yokota et al, 2012).…”
Section: Raoultella Planticola Bacteraemiasupporting
confidence: 90%
See 2 more Smart Citations
“…Similarities of our case to the six summarized by Yokota et al (2012) and the additional four reported by other authors (Castanheira et al, 2009;Kim et al, 2012;Teo et al, 2012) include an association with invasive procedures or trauma (8/11, ERCP in two), an intraabdominal focus (4/11, cholangitis/ cholecystitis in three) and malignancy (3/11). Of the ten previously reported cases of infection due to R. planticola, five involved a monobacterial bacteraemia (Castanheira et al, 2009;Freney et al, 1986;Yokota et al, 2012).…”
Section: Raoultella Planticola Bacteraemiasupporting
confidence: 90%
“…Of the ten previously reported cases of infection due to R. planticola, five involved a monobacterial bacteraemia (Castanheira et al, 2009;Freney et al, 1986;Yokota et al, 2012). Unique to our case is the involvement of this organism in a polymicrobial bacteraemia in the presence of cholangitis and ERCP.…”
Section: Raoultella Planticola Bacteraemiamentioning
confidence: 50%
See 1 more Smart Citation
“…Three patients who developed bacteraemia died, due to multi-drug resistance strains. Various authors suggest at least four possible scenarios that could make a patient develop an infection with this pathogen: (a) inoculation of a significant load of bacteria in a immunologically and/or anatomically injured site, due to trauma in a contaminated environment (community acquired; O'Connell et al 2010;Kim et al 2012); (b) introduction of the pathogen through invasive hospital procedures (nosocomial infection; Freney et al 1984;Kim et al 2012; (c) activation of dormant colonies in immunocompromised patients (Alves et al 2007;Yokota et al 2012) (d) enteric fever and bacteraemia in immunocompetent individuals (fish poisoning; Puerta-Fernandez et al 2013). Extended post-hoc anamnesis did not reveal any recent fish intake (though he had close contact with farm animals) or particular trauma prior to chemotherapy, which makes reactivation of dormant colonies the most probable mechanism in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen bacteremia cases were found in the literature, of which four included cholangitis. It usually affects people with significant co-morbidities (usually immunosuppressed individuals) related to trauma and/or prior invasive procedures (1)(2)(3)(4). Prognosis is good as the pathogen is sensitive to most antibiotics, although resistance has already been reported (5).…”
Section: Discussionmentioning
confidence: 99%